(untitled) (Journal of Medical & Health Sciences Review, 2025)
Global health organizations greatly influence health education and policy for disease prevention. Especially for infectious diseases like COVID-19, Ebola, and influenza, the World Health Organization’s (WHO) Global Health Security Agenda (GHSA) is a vital policy framework meant to enhance countries’ capacity to prevent, identify, and react to public health emergencies. The GHSA weathers global health security by strengthening it through improved disease detection, epidemic response, and healthcare system resiliency.The training addressed health system improvement, disease monitoring, outbreak response, and health promotion and education initiatives for both healthcare providers and the general public. Objective: To investigate how programs global health companies use health education and policy affect disease prevention results. Methods:This research employed a mixed-methods approach combining qualitative and quantitative. Using a survey questionnaire, data on participants’ views of the health policy and educational programs of international health organizations, including training courses on disease prevention and control, health promotion and education, and the use of mobile health (mHealth) technology, was compiled, the study of the experiences of 500 healthcare professionals from 10 different global health organizations with diseases like COVID19, Ebola, and influenza included a sample of The survey was carried out on a safe online platform. Aside from the extensive interviews with 20 key stakeholders, the research acquired more in-depth data. Quantitative data analysis in the study was done using SPSS software; qualitative data analysis was done using NVivo software. Results:The findings show that for COVID19, Ebola, and influenza, the health policy and education initiatives of international health agencies including training courses for disease prevention and control, health promotion and education, and the use of mHealth technologies greatly improved disease prevention results. Particularly, the research revealed that the GHSA enhanced preparedness and response activities for these diseases, therefore strengthening management and control.